PENGALAMAN SEXTING PEREMPUAN MUDA DI INDONESIA DALAM KACAMATA STANDPOINT THEORY - Wolter, Michael (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
ABSTRACT Sexting is the activity of sending sexually charged messages, whether in the form of photos, videos, or even short messages, carried out via digital media. Sexting activities are usually carried out by male and female couples who are in a romantic relationship. In this context, sexting is done to maintain the quality of the relationship and fulfill the partner's sexual needs. However, there is an imbalance of power between women and men involved in sexting, where women are vulnerable to finding themselves in a disadvantageous position compared to men. Through the perspective of standpoint theory, the experience of women as a marginalized group in sexting activities is an important experience to explore. In standpoint theory, those in marginalized positions are considered to have strong objectivity, so the search for knowledge according to this theory should start from these marginalized groups. Through in-depth interviews with informants, this research found that women are in an inferior position when sexting with men. The informants' experiences showed that male partners were forced to engage in sexting, threatened with sharing sexting content, threatened with the end of the relationship, and felt that sexting was more beneficial for men than women. This research concludes that through the lens of standpoint theory, women do feel injustice in sexting activities with male partners, but still do it in order to maintain their relationship through coercion and avoid bad consequences such as the distribution of sexts. Keywords : Sexting; Standpoint Theory; Women; Domination